The relationship between dietary perceptions, and self-care management and dietary adherence among ptients with diabetes mellitus at the Mekar Community Health Center - Michelin Alfa Saruran; Devi Savitri Effendy; La Ode Muhamad Sety (PT WIM Solusi Prima, 2026)
Dietary adherence among patients with diabetes mellitus is a key determinant of successful diabetes management. Dietary management is a self-directed approach that can help prevent complications in patients with diabetes mellitus. Factors such as negative perceptions of diet, weak social support from family, and self-care management influence patients’ adherence to their diet. This study aims to determine the relationship between dietary perceptions (vulnerability, severity, and benefits), family support, and self-care management on dietary compliance among patients with diabetes mellitus at the Mekar Community Health Center in Kendari City, Southeast Sulawesi. This study employed an analytical observational design with a cross-sectional approach. The study sample consisted of 136 respondents selected using consecutive sampling. The dependent variable in this study was dietary compliance, while the independent variables were dietary perceptions (perceived sussceptibility, perceived severity, and perceived benefits), family support, and self-care management. Descriptive analysis revealed that 88 respondents adhered to the diet, while 48 respondents did not adhere to the diabetes diet. Data analysis was performed using bivariate analysis with the Chi-Square test at a significance level of α = 0.05. The results of the study showed that there was a significant relationship between perceived severity (p-value = 0.036), perceived benefits (p-value = 0.006), family support (p-value = 0.046), and self-care management (p-value = 0.036) with dietary adherence in patients with diabetes mellitus. However, there was no significant relationship between perceived vulnerability and dietary compliance (p-value = 0.547). Based on these results, it can be concluded that the factors of perceived severity, perceived benefits, family support, and self-care management play a role in improving patients’ dietary compliance. Therefore, educational interventions focused on enhancing positive perceptions of the diet and strengthening family support are needed to improve patients’ adherence to the diet.